2008
DOI: 10.1126/science.1161527
|View full text |Cite
|
Sign up to set email alerts
|

The Miller Volcanic Spark Discharge Experiment

Abstract: Miller's 1950s experiments used, besides the apparatus known in textbooks, one that generated a hot water mist in the spark flask, simulating a water vapor-rich volcanic eruption. We found the original extracts of this experiment in Miller's material and reanalyzed them. The volcanic apparatus produced a wider variety of amino acids than the classic one. Release of reduced gases in volcanic eruptions accompanied by lightning could have been common on the early Earth. Prebiotic compounds synthesized in these en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
274
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(280 citation statements)
references
References 7 publications
3
274
0
3
Order By: Relevance
“…Accordingly, we examined the reaction of 2-aminothiazole (7) with aldehydes and ketones 2d-w, which are all prebiotic amino acid precursors. 2,[8][9][10][11][12][13] All of the aldehydes furnished their aminals (8d-w) in excellent yield (Table 1). In stark contrast, no ketone aminals precipitated, even after extended incubation.…”
Section: Selective Synthesis Of Pentose Aminooxazoline (1) From a Commentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we examined the reaction of 2-aminothiazole (7) with aldehydes and ketones 2d-w, which are all prebiotic amino acid precursors. 2,[8][9][10][11][12][13] All of the aldehydes furnished their aminals (8d-w) in excellent yield (Table 1). In stark contrast, no ketone aminals precipitated, even after extended incubation.…”
Section: Selective Synthesis Of Pentose Aminooxazoline (1) From a Commentioning
confidence: 99%
“…However, no reported prebiotic synthesis or meteoritic amino acid sample provides the restricted set of amino acids assigned to the genetic code. 2,[8][9][10][11][12][13] For example, Sutherland and co-workers recently demonstrated the stepwise prebiotic syntheses of 12 aminonitrile (13) proteinogenic amino acid precursors, but paradoxically, essential ketones-such as acetone (2o), monohydroxyacetone (2p) and dihydroxyacetone (2q)-are required during assembly of the branched carbon framework of valine and leucine. 13 Ideally ketones would be excluded from prebiotic aminonitrile 13 synthesis because prebiotic ketones undergo aminonitrile formation just as effectively as aldehydes, but α,α-disubstituted amino acids are not genetically encoded (Table 1).…”
Section: Selective Synthesis Of Pentose Aminooxazoline (1) From a Commentioning
confidence: 99%
“…Analyses of the vials from the original experiment reported in Science in 1953 revealed that thirteen amino acids and five amines had been synthesized compared to the seven amino acids Miller had reported (Table 1). In addition, analyses of the vials from the «volcanic» apparatus showed that twenty-one amino acids had been synthesized along with five amines (Johnson et al, 2008 We next turned our attention to boxes of vials from experiments carried out in 1958. For reasons that are unknown, as far as we could ascertain, Miller had never analyzed these after the experiment was carried out.…”
Section: Monographmentioning
confidence: 99%
“…(ii) G 2 is able to duplicate and grow through the classical operations such as mutation, insertion, deletion, inversion and translocation (Faraut & Demongeot 2000) with nucleic material already present in the environment, for example, nucleic bases synthesized from Miller's type reaction (Johnson et al 2008), and to export small RNA fragments to G 1 .…”
Section: Beyond a Common Fitness Function Between Rna Relics Viral Gmentioning
confidence: 99%